Pengembangan e-Modul Elektrokimia Terintergasi Lingkungan Berbasis Kontekstual Untuk SMK Kompetensi Keahlian Teknik Otomotif - Agung Purwanto; Muktiningsih Nurjayadi; Johanes Erwin Tantaruna (Jurnal Riset Pendidikan Kimia (JRPK), 2020)
This study aims to produce electrochemical learning e-module as environmentally integrated contextual teaching materials for students of Vocational Automotive Engineering Competency. This research was conducted at SMK Negeri 26 Jakarta during the even semester of the 2018/2019 school year. The method used is the Research and Development method. Respondents in this study were vocational students, lecturers, and teachers. The results of the interpretation of the material and linguistic feasibility test of 74% - 87% with a value of r = 0,93 indicate that the e-module is very good in terms of the feasibility of the content and the feasibility of the presentation. While the results of the interpretation of the media feasibility test 76% - 89% with a value of r = 0,94 shows that the e-module is very good in terms of e-module size, e-module skin design, and e-module content design. Based on the assessment of students in small group trials, e-modules were corrected and re-tested in large groups and an interpretation of 72% - 90% showed that the e-modules were very good in terms of material feasibility and feasibility of presentation. Based on the evaluation of teacher trials obtained an interpretation of 84% - 100% with a value of r = 0,81 which shows the e-module is very good. The results of the excellent interpretation show that the electrochemical e-module for the Vocational High School of Automotive Engineering Skills is appropriate to be used as teaching material.